UR_GERICHTE 2016_OG V 15 44. vom 26. August 2016 - UR Obergericht (2016)
Wasserrecht. Art. 41 WRG. Art. 18 Abs. 3, Art. 48 GNG. Art. 2 Abs. 1, Art. 2c-2e, Art. 10 Abs. 2 GNV. Art. 55 Abs. 1 lit. e und Abs. 2, Art. 83 Abs. 1 VRPV.